Effects of porous flow field type separators using sintered Ni-based alloy powders on interfacial contact resistances and fuel cell performances. (1st July 2015) - Kariya, Tetsuro; Yanagimoto, Katsu; Funakubo, Hiroshi; Shudo, Toshio
Abstract: The novel separators with a porous flow field using sintered corrosion resistant Ni-base alloy C276 (Ni–16Cr–16Mo–5Fe–4W mass%) powders or SUS316L (Fe–17Cr–12Ni–2Mo mass%) powders are investigated for proton exchange membrane fuel cells to enhance power density, which is one of the most important challenges for the widespread use of fuel cells. The developed separator with C276 powders demonstrated low ICRs (interfacial contact resistance) less than 10 mΩ cm 2 between separators and GDLs (gas diffusion layers), and it extensively enhanced power density by 90% higher than a conventional graphite separator. This is due to the superior adherence mechanism between the convex surfaces of the spherical powders and porous GDLs as well as the Ni concentration in passive oxide films in powder surfaces. Furthermore, this developed separator shows potential for using without an expensive conductive coating such as Au coating, which has been usually employed to lower ICRs for metallic separators with passive oxide films. In addition, the amount of eluted Cr, which could deteriorate catalyst and cell performance, from sintered C276 powders in a 1 mass% sulfuric acid aqueous solution is reduced by approximately 82% than SUS316L powders. Highlights: A flow field of sintered Ni alloy powder reduces interfacial contact resistance. A separator with a porous flow field of Ni alloy powders enhances cell performance. Vacuum sintered Ni alloy powders show superior corrosion resistance. Sintered Ni alloy separators without gold coating show good cell performance.